Proceedings of the 34th International ACM SIGIR Conference on Research and Development in Information Retrieval 2011
DOI: 10.1145/2009916.2010002
|View full text |Cite
|
Sign up to set email alerts
|

Fast context-aware recommendations with factorization machines

Abstract: The situation in which a choice is made is an important information for recommender systems. Context-aware recommenders take this information into account to make predictions. So far, the best performing method for contextaware rating prediction in terms of predictive accuracy is Multiverse Recommendation based on the Tucker tensor factorization model. However this method has two drawbacks:(1) its model complexity is exponential in the number of context variables and polynomial in the size of the factorization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
270
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 481 publications
(273 citation statements)
references
References 22 publications
1
270
0
2
Order By: Relevance
“…In contrast to the previous two methods, the contextual modeling method uses all the contextual and user-item information simultaneously to make predictions. More recent works have focused on the third method [10,13,24,27]. Karatzoglou et al [10] proposed Multiverse Recommendation model in which the different types of context are considered as additional dimensions in the representation of the data as a tensor.…”
Section: Context-aware Recommendationmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast to the previous two methods, the contextual modeling method uses all the contextual and user-item information simultaneously to make predictions. More recent works have focused on the third method [10,13,24,27]. Karatzoglou et al [10] proposed Multiverse Recommendation model in which the different types of context are considered as additional dimensions in the representation of the data as a tensor.…”
Section: Context-aware Recommendationmentioning
confidence: 99%
“…However, for real-world scenarios its computational complexity is too high. Rendle [24] showed that Factorization Machines (FM) model can be applied to context-aware recommendation because that a wide variety of context-aware data can be transformed into prediction task using real-valued feature vectors. Nguyen et al [16] developed a nonlinear probabilistic algorithm for context-aware recommendation using Gaussian processes which is called Gaussian Process Factorization Machines (GPFM).…”
Section: Context-aware Recommendationmentioning
confidence: 99%
See 2 more Smart Citations
“…With the prevalence of smart mobile devices [6], the consumers' clickstream data have been enriched with various contextual information [25], such as geographical information, which poses significant new opportunities as well as challenges [13]. Some data mining techniques have been employed to extract consumers' context-aware preferences [12,20]. However, these research efforts mostly focused on purchase records while ignoring the search activities.…”
Section: Introductionmentioning
confidence: 99%